The Issues of Racism in the Novel Between The World and Me by Ta-Nehisi Coates - Triani, Anita (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2022)
One of the issues that attracted public attention recently regarding American culture is racism. It is a belief system or theory known as racism that holds that a certain race is superior and has the right to govern over other races and that biological differences between human races dictate cultural or individual achievements. This can occur in the majority between the black and the white race. Racism has occurred since time immemorial and has become a historical thing in the United States. This phenomenon is published in various forms, both literary and scientific works. One of them is the novel Between the World and Me by Ta-Nehisi Coates, which discusses the issues of racism that he experienced. The issues in this novel include the difficulty of living in school as a black student and the different treatment of black people in terms of law and security.